2019
DOI: 10.1016/j.cmi.2019.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Trained innate immunity and resistance to Mycobacterium tuberculosis infection

Abstract: a b s t r a c tBackground: Some individuals, even when heavily exposed to an infectious tuberculosis patient, develop neither active nor latent tuberculosis infection (LTBI). This 'early clearance' of Mycobacterium tuberculosis is associated with a history of bacillus CalmetteeGu erin (BCG) vaccination. As BCG vaccination can boost innate immune responses through a process termed 'trained immunity', we hypothesize that BCGinduced trained innate immunity contributes to early clearance of M. tuberculosis. Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 33 publications
0
70
0
Order By: Relevance
“…Notwithstanding, the central role by AM in taking up M.tb , particularly in early phases of infection 43,45 offers an opportunity to exploit the concept of TII to immunologically manipulate the phenotype of AM prior to M.tb exposure 2,3,10,55–57 . For instance, immunologically rewiring the metabolic profile of AM 13 toward a highly glycolytic capacity represents such a strategy amenable to robust bactericidal control of M.tb 42 .…”
Section: Innate Immune Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, the central role by AM in taking up M.tb , particularly in early phases of infection 43,45 offers an opportunity to exploit the concept of TII to immunologically manipulate the phenotype of AM prior to M.tb exposure 2,3,10,55–57 . For instance, immunologically rewiring the metabolic profile of AM 13 toward a highly glycolytic capacity represents such a strategy amenable to robust bactericidal control of M.tb 42 .…”
Section: Innate Immune Tolerancementioning
confidence: 99%
“…In so doing, trained AM will be able to overcome the innate immune tolerogenic/suppressive effects of M.tb upon exposure for enhanced innate protection. Indeed, it has been observed that up to 20% of the human house contacts exposed to M.tb could quickly clear infection (early clearers) as judged by lack of conversion in the interferon‐gamma‐release assay and purified protein derivative skin test, 55 and such protection is associated with increased innate immune responses and BCG vaccination 58,59 …”
Section: Innate Immune Tolerancementioning
confidence: 99%
“…Benn and Aaby [9] describe in an historical review how epidemiologic studies in many industrialized and low-income countries led to the concept of beneficial nonspecific effects of BCG and other live human vaccines. Koeken et al [10] discuss the epidemiologic evidence and biologic concepts of early clearance of M. tuberculosis by BCG vaccination. They hypothesize that vaccination with BCG or other strategies to induce trained immunity could prevent TB contacts from becoming infected.…”
mentioning
confidence: 99%
“…Results indicate that BCG re-vaccination reduces the rate of sustained Quanti-FERON (QFT) conversion and displays improved long-term innate or trained immunity and adaptive responses, thus leading to effective control of mycobacterial infection. [123][124][125][126][127][128][129] A comprehensive review by Schaible et al in 2017 evaluates strategies to improve vaccine efficacy against TB by targeting innate INF-γ interferon-γ, TNF-α tumor necrosis factor-α, GM-CSF granulocyte/macrophage-colony stimulating factor, VEGF vascular endothelial growth factor, Ang angiopoietin, IL interleukin, DCs dendritic cells, CD cluster of differentiation, JAK-STAT Janus tyrosine kinase-signal transducer and activator of transcription, TGF-β transforming growth factor-β; BCG = Bacille Calmette Guerin, CFU colony-forming units, MGIT Mycobacteria Growth Indicator Tube a No clinical trial data as evidence for therapeutic intervention potential and outcome in TB disease immunity. 130 Here, they propose that short-term modulation of the local immune response to BCG vaccination may result in longterm protective immunity against Mtb infection.…”
Section: Cytokinementioning
confidence: 99%